Kelebihan, Kekangan dan Penerimaan Sistem Pilihanraya Berkomputer Yang Menggunakan Cap Jari Digital di Institut Pengajian Tinggi - Norshuhaida, Ismail (2003)
The main objective of this paper is to investigate the pros and cons, and the acceptance of the university students towards computerized voting. Before the data analysis can be done, a system prototype was build using the C++ program language. This system uses biometric technology in the verification process. This prototype’s verification process will scan the fingerprint which is stored in the voter’s smartcard. While in the voting process, computerized voting system was used to replace pens and papers. The entire respondents were chosen among the university students around the state of Selangor. Respondents were asked to test the system prototype and afterwards, fulfilled a survey regarding that system prototype.